Characterisation of a Monoclonal Antibody to von Willebrand Factor as a Potent Inhibitor of Ristocetin-Mediated Platelet Interaction and Platelet Adhesion - Jorieux, Sylvie; de Romeuf, Christophe; Samor, Bruno; Goudemand, Maurice; Mazurier, Claudine (Thrombosis and Haemostasis, 1987)
We studied a murine monoclonal antibody (211 A6) to von Willebrand factor (vWF) with a view to investigating structure-relationship. of plasma vWF. The specificity of this antibody has been substantiated by ELISA tests and indirect immunofluorescence. It reacts with purified vWF, normal plasma but not with plasma or platelets from a severe von Willebrand’s disease patient. Monoclonal antibody 211 A6 is a potent inhibitor of ristocetin-induced platelet aggregation. The 125I-FVIII/vWF binding to platelets in presence of ristocetin is totally inhibited by low 211 A6 concentrations. Thrombin-induced binding of vWF to platelets is not affected by 211 A6. The ability of this antibody to inhibit platelet adhesion to subendothelium and to collagen was investigated with a perfusion model. The complete inhibition of platelet adhesion by 211 A6 questions the similarity or the interrelationship in vWF domains involved in ristocetin-induced platelet functions and platelet adhesion.
Keywords: Monoclonal antibody; von Willebrand factor; Ristocetin cofactor; Platelet adhesion